Experimental Study on CO2 Heat Pump Thermal Battery System - Zhu Weiquan; Liu Fang; Cai Yang (Zhileng xuebao)
CO2 heat pump thermal battery system consists of a water-source transcritical carbon dioxide heat pump coupled with hot and cold thermal storage, and its performance gradually decreases during the process of thermal energy storage. This paper presents experimental studies of a CO2 heat pump thermal battery system. The performance of this system was tested under a variable water-circulation flow rate for the hot/cold tank, a variable compressor frequency, and electronic expansion valve (EEV) opening. The results show that adoption of a lower water-circulation flow rate allows the tank to obtain good thermal stratification and a larger capacity. Further, a high compressor frequency benefits the system performance. The EEV opening also influences the system performance. The overall coefficient of performance (COP) reaches a maximum of 5.49 when the compressor frequency is 50 Hz, the EEV opening is 330 pulse, and the hot and cold water flow rates are 0.1 and 0.2 m3/h, respectively. Moreover, through mathematical fitting, a correlation was established between the COP, the outlet temperatures of the hot and cold tanks, and the control parameter. Overall, the total COP is 6.29 when the optimal control strategy based on the genetic algorithm is applied.